ISOTOPIC ANALYSES REVEAL GEOGRAPHICAL AND SOCIOECONOMIC PATTERNS IN HISTORICAL DOMESTIC ANIMAL TRADE BETWEEN PREDOMINANTLY WHEAT- AND MAIZE-GROWING AGRICULTURAL REGIONS IN EASTERN NORTH AMERICA. Issue 2 (29th March 2017) - Guiry, Eric; Szpak, Paul; Richards, Michael P.
Abstract : Historical zooarchaeologists have made significant contributions to key questions about the social, economic, and nutritional dimensions of domestic animal use in North American colonial contexts; however, techniques commonly employed in faunal analyses do not offer a means of assessing many important aspects of how animals were husbanded and traded. We apply isotopic analyses to faunal remains from archaeological sites to assess the social and economic importance of meat trade and consumption of local and foreign animal products in northeastern North America. Stable carbon and nitrogen isotope analyses of 310 cattle and pigs from 18 rural and urban archaeological sites in Upper Canada (present-day southern Ontario, Canada; ca. A.D. 1790–1890) are compared with livestock from contemporary American sources to quantify the importance of meat from different origins at rural and higher- and lower-status urban contexts. Results show significant differences between urban and rural households in the consumption of local animals and meat products acquired through long-distance trade. A striking pattern in urban contexts provides new evidence for the social significance of meat origins in historical Upper Canada and highlights the potential for isotopic approaches to reveal otherwise-hidden evidence for social and economic roles of animals in North American archaeology. Abstract : Les zooarchéologues travaillant sur la période historique ont apporté d'importantes contributions à des questions-clés sur les dimensions sociales, économiques et nutritionnelles de l'utilisation des animaux domestiques dans les sites coloniaux d'Amérique du Nord. Cependant, les techniques couramment utilisées dans les analyses fauniques ne permettent pas d'aborder plusieurs aspects concernant l'élevage et l'échange d'animaux. Nous appliquons des analyses isotopiques sur les restes fauniques provenant de sites archéologiques pour évaluer l'importance sociale et économique du commerce de la viande et de la consommation de produits animaliers d'origine locale et étrangère dans le Nord-Est américain. L'analyse des isotopes stables de carbone et d'azote sur 310 bovins et porcs provenant de 18 sites archéologiques ruraux et urbains dans le Haut-Canada (aujourd'hui le sud de l'Ontario, Canada, entre 1790–1890 A.D.) sont comparées avec le bétail provenant de sources américaines contemporaines afin de quantifier l'importance de la viande de différentes origines dans les sites ruraux et dans les contextes urbains représentant des occupations de statut élevé et moins élevé. Les résultats démontrent que des différences significatives existent entre les maisonnées urbaines et rurales dans la consommation d'animaux d'origine locale et les viandes acquises par le commerce à longue distance. Une différence marquée dans les contextes urbains fournit de nouvelles informations quant à l'importance sociale des origines de la viande dans le Haut-Canada durant la période historique et souligne le potentiel des approches isotopiques pour révéler des informations autrement cachées sur les rôles sociaux et économiques des animaux en archéologie nord-américaine.